Research training and attitude towards scientific research in social sciences students from the Universidad Nacional del Centro del Perú - Bullón López, Elena (2019)
The purpose of this research was to determine and know the relationship between the level of research training and the level of attitude toward scientific research in social science students from the Universidad Nacional del Centro del Perú. The research level was descriptive-correlational non-causal, basic type, non-experimental cross-sectional correlational ex-post-facto design; the instruments were a test for the variable of research training and the Likert scale inventory for the variable of attitude towards scientific research. For the validity of the instruments, 5 experts' judgment was applied and the results with the Cronbach’s alpha model (α = 0.796). For the reliability, the pilot test was used and the results obtained with the same model (α = 0.7654). The units of analysis were the students from the tenth semester of the careers of Anthropology, Communication Sciences, Sociology and Social Work; the study population was of 1493 students, and the sample, non-probabilistic and intentional type, of 141. The result for the demonstration of the relationship between the level of research training and the level of attitude toward scientific research was performed by linear regression, accepting that there is no relationship. It was concluded that there is no significant relationship between the study variables.   DOI: https://doi.org/10.31876/sl.v3i2.10